Technological strategies to improve gelation properties of legume proteins with the focus on lupin. (March 2021) - Al-Ali, Hayder A.; Shah, Umar; Hackett, Mark J.; Gulzar, Muhammad; Karakyriakos, Emmanuel; Johnson, Stuart K.
Abstract: There is a growing demand for plant protein due to the increasing number of consumers looking for healthier food options. Protein from the legume seed lupin is a viable plant protein source due its high protein content and agricultural sustainability of lupin production. Lupin protein is however underutilised in food manufacturing due to its poor gelling and thickening properties. This review uncovers the link between lupin protein structural properties and its poor gelling functionality. It will compare lupin with other legume proteins in terms of protein structure and gel quality. Current knowledge of legume protein gelation processes, factors controlling gelation mechanisms and methods for evaluating gel quality will be presented. Finally, green and efficient protein modification technologies to improve gelation will be detailed. This review also reveals the scarcity of information on approaches to improve the poor gelation properties of lupin protein, highlighting the need for research in this area. Highlights: Lupin as an abundant source of protein for human food manfacturing. The influence of unique lupin protein structure on its poor gelation properties. The potential novel physical protein modification treatment on improving lupin protein gel quality. Some of these new methods required more research to understand their effect on legume protein structural changes and gel quality.